Ethical theories in Islam - Fakhry, Majid (Islamic philosophy, theology, and science, 1994)
This book consists of a systematic analysis of the basic concepts of Islamic ethics and is based on a vast amount of material in Arabic which is not easily accessible to Western scholars, especially those who have no knowledge of the Arabic language.